An Efficient Synthesis of Pemetrexed Disodium. (17th July 2014) - Qi, H.; Wen, J.; Li, L.; Bai, R.; Chen, L.; Wang, D.
<x xml:space="preserve">Abstract</x> An efficient synthetic method for the pemetrexed disodium has been developed using methyl 4‐iodobenzoate and 3‐buten‐1‐ol as starting materials via six steps. The developed process avoided some tedious workup procedures and unfriendly reagents compared with the reported synthetic routes. In addition, two impurities generated in the process were isolated and characterized by 1H NMR, 13C NMR, and HRMS. The mechanisms of the two impurities were also discussed, and the impurities could be easily removed by suitable workup procedures. The overall yield of pemetrexed disodium was increased from 12.8% (literature) to 34.9%. Therefore, this cost‐effective, environmental friendly, and high‐yielding process is more suitable for scale‐up production of pemetrexed disodium.